TELEGRAPHS TO INCANDESCENT LAMPS: A SEQUENTIAL PROCESS OF INNOVATION - Laurence Malone (Essays in Economic and Business History, 2000)
This paper outlines a sequential process of technological innovation in the emergence of the electrical industry in the United States from 1830 to 1880. Successive inventions that realize the commercial possibilities of electricity provided the foundation for an industry where technical knowledge, invention and diffusion were ultimately consolidated within the managerial structure of new firms. The genesis of the industry is traced, sequentially, through the development of the telegraph, arc light and incandescent lamp. Exploring the origins of the telegraph and incandescent lamp reveals a process where a series of inventions and firms result from successful efforts touse scientific principles to create new commodities and markets.